Compartment Syndrome of the Foot – Implications for Military Surgeons. Issue 4 (1st December 2010) - Middleton, Simon; Clasper, J
Abstract : Introduction: Compartment syndrome of the foot is a rare complication of injury to the foot. Treatment by decompression of the compartments is debatable. The debate surrounding decompression stems from the rarity of the condition, the lack of consensus regarding the anatomy of the foot compartments and whether to accept the inevitable contractures by not decompressing. The aim of this paper is two fold; firstly to sample current military orthopaedic experience and secondly establish if there exists a consensus of opinion in how and if to perform fasciotomy of the foot thereby providing guidance to other clinicians. Method: A questionnaire was sent to 10 DMS orthopaedic consultants to identify their experience with foot compartment syndrome and performing foot fasciotomies. Results: Five had performed a foot fasciotomy (average 2, range 1-6) over an average of 6.2 years as consultant and an average of 7.3 months deployed. Most commonly two dorsal and a medial incision were used to decompress the foot. One surgeon advocated not decompressing the foot and accepting the subsequent contractures, Conclusion: DMS clinicians need to remain vigilant to compartment syndrome of the foot and especially in cases of crush or blast injury or of multiple fractures. If diagnosed or even if an impending compartment syndrome is suspected then, in line with the current weight of expert opinion, the foot should be decompressed and the deployed orthopaedic surgeon should be capable of performing it. Evidence concerning their battlefield use is limited. Extensive UK military trials are ongoing and the results of which are expected to clarify questions regarding complication rate and efficacy.